The protease inhibitor cystatin C downregulates the release of IL-β and TNF-α in lipopolysaccharide activated monocytes - Thiesen, Susanne; Janciauskiene, Sabina; Sandeep, Salipalli; Jonigk, Danny; Kvist, Peter Helding; Gerwien, Jens Gammeltoft; Håkansson, Katarina; Grip, Olof (Journal of Leukocyte Biology, 2016)
Human cystatin C, a member of the cysteine proteinaseinhibitory family, is produced by all nucleated cells and has important roles in regulating natural immunity. Nematode homologs to human cystatin C have been shown to have anti-inflammatory effects on monocytes and to reduce colitis in mice. In Crohn’s disease, pathogenic activated monocytes help drive inflammatory processes via the release of proinflammatory cytokines and chemokines. In particular, tumor necrosis factora-producing inflammatory monocytes have a central role in the intestinal inflammation in patients with Crohn’s disease. We investigated the potential of human cystatin C to regulate pathogenic activated monocytes and its potential as an Immunomodulator in Crohn’s disease.We found that cystatin C significantly decreased the lipopolysaccharide-stimulated release and expression of interleukin-1b and tumor necrosis factor-α in monocyte and peripheral blood mononuclear cell cultures from healthy donors, whereas interleukin-6 and interleukin-8 levels were unchanged. A similar reduction of interleukin-1b and tumor necrosis factor-α was also seen in peripheral bloodmononuclear cell cultures from patientswith Crohn’s disease, and in particular, tumor necrosis factor-α was reduced in supernatants from lamina propria cell cultures from patients with Crohn’s disease. Further investigation revealed that cystatin C was internalized by monocytes via an active endocytic process, decreased phosphorylation of the mitogen-αctivated protein kinase pathway extracellular signal-regulated kinase-1/2, and altered surface marker expression. The ability of cystatin C to modulate the cytokine expression of monocytes, together with its protease-inhibitory function, indicates that modulation of the local cystatin C expression could be an option in future Crohn’s disease therapy.
Keywords: Crohn’s disease; Cytokines; Immunomodulator; Inflammation; Monocytes